Tick paralysis cases in Argentina - Remondegui,Carlos (2012)
Tick paralysis (TP) occurs worldwide and is caused by a neurotoxin secreted by engorged female ticks that affects the peripheral and central nervous system. The clinical manifestations range from mild or nonspecific symptoms to manifestations similar to Guillain-Barré syndrome, bulbar involvement, and death in 10% of the patients. The diagnosis of TP is clinical. To our knowledge, there are no formal reports of TP in humans in South America, although clusters of TP among hunting dogs in Argentina have been identified recently. In this paper, clinical features of two cases of TP occurring during 1994 in Jujuy Province, Argentina, are described.